Effects of interactivity and progressive visuospatial cues on learners' comprehension of dynamic visualizations. Issue 2 (3rd April 2021) - Yang, Hui-Yu
Abstract: The present empirical study investigated whether progressive visuospatial cues presented in a self-regulatory mode could assist learners in comprehending the operation of a mechanical system. In the present study, the interactivity and cueing were the independent variables in terms of investigating their effectiveness on retention and transfer test results. Dynamic visualizations enriched with visuospatial cues in either system-paced or self-regulatory presentation modes served as the instructional materials. A total of 269 English as a foreign language (EFL) learners voluntarily participated in the experiment. First, their prior knowledge was assessed. Next, they were assigned to one of six experimental conditions—animation-only, entity-cued animation, and arrow-entity-cued animation in either self-regulatory or system-paced modes. Right after learning the instructional visualizations, retention and transfer tests regarding the operation of the mechanical system and a cognitive load questionnaire were administered to evaluate the learners' test performance and cognitive load, respectively. The experimental results suggested that progressive snowball-like cues were advantageous in helping learners discriminate between task-relevant and task-irrelevant components with respect to the operation of a mechanical system as reflected by the learners' retention and transfer test results. The experimental results suggested that progressive snowball-like cues under the self-regulatory mode assisted the learners in achieving both local and global comprehension.